2021
DOI: 10.3390/nu13010206
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, Quercetin, Catechins and Metabolic Diseases: The Role of Gut Microbiota

Abstract: Polyphenols (PPs) are the naturally occurring bioactive components in fruits and vegetables, and they are the most abundant antioxidant in the human diet. Studies are suggesting that ingestion of PPs might be helpful to ameliorate metabolic syndromes that may contribute in the prevention of several chronic disorders like diabetes, obesity, hypertension, and colon cancer. PPs have structural diversity which impacts their bioavailability as they accumulate in the large intestine and are extensively metabolized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 180 publications
(88 reference statements)
0
126
0
Order By: Relevance
“…The GM may contribute to metabolic health, but dysbiosis in GM composition triggers metabolic syndrome. Metabolic syndrome is a combination of abnormalities contributing to different diseases such as malnutrition, non-alcoholic liver disease, obesity, cardio-metabolic diseases and type-2 diabetes [4,62,63]. Deficiency of SIRT3, known as a mitochondrial deacetylase, is a significant cause of metabolic syndrome.…”
Section: Metabolic Impairment and Admentioning
confidence: 99%
See 1 more Smart Citation
“…The GM may contribute to metabolic health, but dysbiosis in GM composition triggers metabolic syndrome. Metabolic syndrome is a combination of abnormalities contributing to different diseases such as malnutrition, non-alcoholic liver disease, obesity, cardio-metabolic diseases and type-2 diabetes [4,62,63]. Deficiency of SIRT3, known as a mitochondrial deacetylase, is a significant cause of metabolic syndrome.…”
Section: Metabolic Impairment and Admentioning
confidence: 99%
“…The Mediterranean diet is deemed beneficial for AD patients as it is rich in many components such as legumes, fruits, vegetables, cereals, polyphenols, non-digestible carbohydrates, and unsaturated fatty acids [107]. Polyphenols (PPs) are naturally occurring bioactive compounds and the most abundant forms of antioxidants in the human diet [63]. PPs have been recognized as potent agents that can lower the risk of AD [13].…”
Section: Diet and Food Componentsmentioning
confidence: 99%
“…It is a dietary flavonoid found in fruits (mainly citrus), many seeds (buckwheat), and so on [ 53 ]. Present studies have provided evidence that quercetin improves gut health and helps alleviate metabolic disorders, which is likely to be one reason why the millet porridge is effective for children’s diarrhea [ 54 ]. Most of the quercetin existed in YG1, and a small amount was detected in JG21.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, low molecular weight chitosan and enzymatic unsaturated alginate were prepared in our lab and selected as polymer shells. Current studies have shown that Cur is therapeutically effective against UC and regulative effect on gut microbiota (Grammatikopoulou et al., 2018 ; Sadeghi et al., 2020 ; Shabbir et al., 2021 ). Quantitative analysis indicated that CD–Cur–CANPs significantly reversed the decrease in Bifidobacteria and Lactobacilli induced by DSS treatment.…”
Section: Discussionmentioning
confidence: 99%